Diversity, specificity and speciation in larval Diplostomidae (Platyhelminthes: Digenea) in the eyes of freshwater fish, as revealed by DNA barcodes. Issue 13 (November 2015) - Locke, Sean A.; Al-Nasiri, Fatima S.; Caffara, Monica; Drago, Fabiana; Kalbe, Martin; Lapierre, Angela Rose; McLaughlin, J. Daniel; Nie, Pin; Overstreet, Robin M.; Souza, Geza T.R.; Takemoto, Ricardo M.; Marcogliese, David J.
Graphical abstract: Highlights: We used DNA barcodes to survey larval diplostomids in fish eyes across the world. Scalable distance-based analysis of CO1 recovered 52 species (19 newly sequenced). Metacercariae of species of Diplostomum in the lens are less host-specific. Fewer species of Diplostomum have metacercariae in the lens. Lower immune activity in the lens may influence both specificity and speciation. Abstract: Larvae (metacercariae) in some species of Diplostomidae (Platyhelminthes: Digenea) inhabit fish eyes and are difficult to identify to species based on morphology. DNA barcoding has clarified the diversity and life cycles of diplostomids in North America, Europe and Africa, but has seldom been used in parasites sampled in large numbers or at large spatial scales. Here, distance-based analysis of cytochrome c oxidase 1 barcodes and, in some specimens, internal transcribed spacer (ITS-1, 5.8S, ITS-2) sequences was performed for over 2000 diplostomids from Africa, the Middle East, Europe, Asia and the Americas. Fifty-two species of Diplostomum, Tylodelphys and Austrodiplostomum (Digenea: Diplostomidae) were distinguished. The 52 species comprise 12 identified species, six species in two species complexes and 34 putative species, and 33/52 had been delineated in previous studies. Most (23/40) of the unidentified, putative species distinguished by cytochrome c oxidase 1 distances were supported by at least one additional line of evidence. As the intensity of sampling of the 52 species increased, variation in cytochrome c oxidase 1 decreased between and increased within species, while the spatial scale at which species were sampled had no effect. Nonetheless, variation between species always exceeded variation within species. New life-cycle linkages, geographic and host records, and genetic data were recorded in several species, including Tylodelphys jenynsiae, Tylodelphys immer and Diplostomum ardeae . Species of Diplostomum inhabiting the lens are less host-specific and less numerous than those infecting other tissues, suggesting that reduced immune activity in the lens has influenced rates of speciation.